Study of La 4 BaCu 5−x Co x O 13+δ series as potential cathode materials for intermediate-temperature solid oxide fuel cell - Duran, Silvia; Téllez Bernal, Jhoan Francisco; Sandoval, Mónica V.; Macias, Mario A.; Capoen, Edouard; Pirovano, Caroline; Roussel, Pascal; Niemczyk, Anna; Barrera Castillo, Mónica; Mogni, Liliana Verónica; Suescun, Leopoldo; Gauthier, Gilles H. (Elsevier Science, 2018)
Fil: Duran, Silvia. Universidad Industrial Santander; Colombia. Universidad de la República; Uruguay